Neonatal Ethics Teaching Program - Scenario Oriented Learning in Ethics: Antenatal Consultation at the Limit of Viability - Daboval, T; Ferretti, E; Rohde, K; Muirhead, P; Moore, G (Université d'Ottawa | University of Ottawa, 2015)
Neonatal Ethics Teaching Program – Scenario Oriented Learning in Ethics (SOLE): Antenatal Consultation at the Limit of Viability. SOLE uses standardized patients (SPs) as a teaching tool to impart knowledge on the principal and the 3 key competencies of the Neonatal Ethics Teaching Program that trainees are expected to acquire before completing their Neonatal-Perinatal Medicine (NPM) training at the University of Ottawa. Furthermore, this workshop provides trainees the opportunity to practice and learn how they would interact with a true patient in a given clinical scenario. The goal of this workshop is to help trainees show improvement in their communication skills and demonstrate appropriate application of ethical principles when they have to interact with parents in delicate, difficult, and ethically charged situations regarding their child. Trainees are encouraged to refer to a procedural form that suggests steps to follow during a one on one medical encounter and use the SP as a teaching tool. This SOLE is specific to an antenatal consultation at the limit of viability scenario where trainees are taught to identify areas of potential conflict, explain ways to resolve conflict at the limit of viability, and learn how to facilitate a shared decision making process.